Biotechnology strategies for bioactive compound extraction - Iñiguez-Moreno, Maricarmen; de la Rosa-Flores, Orlando Daniel; Melchor-Martínez, Elda M.; Parra-Saldívar, Roberto (Springer, 2025)
The marine environment is a relatively unexplored source of bioactive compounds that can be used in several industries in various ways. Some organisms live in harsh environmental conditions, resulting in complex compounds with unique biological properties. One of the main challenges for their application into the industry is their extraction, one of the most crucial stages in developing products containing bioactive compounds from marine sources. Soxhlet extraction is the most common method applied at lab and pilot scales to obtain compounds from any natural source. However, this method is based on using solvents that can be harmful to the environment and affect the biological properties of the compounds. For this, biotechnological extraction techniques such as fermentation, enzyme-assisted extraction, and molecular tools have emerged as alternatives to traditional methods that enable the extraction of high-quality bioactive compounds without using harmful solvents. Besides, these technologies have shown great potential to be applied at the industrial scale once the optimization of the process has been carried out. This chapter focuses on the potential use of biotechnological tools for extraction, considering the factors that affect the yields and downstream process of marine-derived bioactive compounds for further applications in the industry.
Keywords: 31 Biological Sciences; 3106 Industrial Biotechnology; Generic health relevance; 14 Life Below Water; Solid-state fermentation; Submerged fermentation; Enzyme-assisted extraction; Purification; Marine bioactive compounds